(untitled) (Revista de Ciências Agroveterinárias, 2025)
The use of bioproducts derived from seaweed has been gaining prominence in agricultural production systems due to their bioactive properties and effects. These products exhibit phytostimulating characteristics that enhance plant growth and improve yield parameters in several important crops. Maize, one of the world’s widely cultivated crops, benefits significantly from the application of seaweed-derived bioproducts due to its susceptibility to various environmental stresses. The aim of this study was to evaluate the foliar application of a bioproduct based on Solieria chordalis (Rhodophyta) on the biosynthesis of photosynthetic pigments and yield of 27 different maize hybrids grown in a Brazilian ecoregion denominated “Cerrado”. This region experiences various types of abiotic stresses such as dry spells and high temperatures. The experiment was conducted at a research station located in Sidrolândia, Mato Grosso do Sul, Brazil, during the second maize harvest season of 2023. The results showed that a singular foliar application of a red seaweed-based product (1.0 L ha-1) at the V6 phenological stage enhanced photosynthetic pigments and yield of most maize hybrids. Foliar application of the red seaweed-based product increased the primary metabolism, thereby boosting the yield of maize plants under field conditions.